POLA KOMUNIKASI SUPPORTER SEPAKBOLA ULTRAS GARUDA SEZIONE RIAU DALAM MEMPERTAHANKAN SOLIDARITAS ANGGOTA - Pasaribu, Raihan Taufik; Susanti, Hevi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This title was raised in accordance with the background thought that basically humans are social creatures, humans essentially have a tendency to live in groups, among others based on hobbies or an activity to fulfill the purpose of these needs by communicating. Thus, the formulation of the problem in this study is: how is the communication pattern of the Garuda Sezione Riau Ultras Supporter community in maintaining the solidarity of its members. This study is purpose to know the communication pattern that happened and developed in Garuda Sezione Riau Ultras Supporter community. This type of research is Descriptive Qualitative research, data collection techniques are carried out by interview, and observation, and documentation. data sources using informants or sources as many as 5 people consisting of coordinators, administrators, and members of the Ultras Garuda Sezione Riau Supporter community which was carried out in a period of 2 months during March to May 2024, with data collection techniques using interviews, documentation and observation. According to the result, it is found that solidarity sense of Garuda Sezione Riau Ultras Supporter member is formed by an intens communication and comprehension about good communication pattern. This matter shows kinship of every member in community Garuda Sezione Riau Ultras Supporter has achieved a deepen level. Communication pattern used by Supporter Ultras Garuda Sezione Riau is the Star model communication pattern or all channels, where all members have the same position in communication activities within the community. While the barriers to ongoing communication are experienced, they do not interfere with the communication process, creating a harmonious and productive environment. Every individual has equal access to information and the opportunity to voice their opinions.